Settlement and Subsistence in the Remote Western Pacific: Archaeological and Radiocarbon Data from Alamagan, Northern Mariana Islands. (17th February 2019) - Athens, J. Stephen; Leppard, Thomas P.
ABSTRACT: Small, remote islands were marginal environments for prehistoric human populations. We report archaeological and radiocarbon data from Alamagan, a small and isolated island in the northern part of the Mariana Islands archipelago. Challenging environmental conditions, including rugged terrain, active or recent volcanism, and uncertain freshwater availability posed significant challenges for permanent settlement throughout the Northern Islands. The Alamagan archaeological investigations documented 14 megalithic domestic structures, or latte sets, as well as isolated and non-portable Latte Period artifacts, and one historical site. Test excavations were undertaken at two of the latte features. These investigations add to a growing body of data suggesting colonization of the Northern Islands during the middle part of the Latte Period (probably during the latea.d. 1200s or early 1300s). We consider the implications of these data for the study of human adaptations to marginal insular environments in the Pacific.